Fibres and asbestos bodies in bronchoalveolar lavage fluids of asbestos sprayers. Issue 7 (July 1992) - Tuomi, T; Oksa, P; Anttila, S; Taikina-aho, O; Taskinen, E; Karjalainen, A; Tukiainen, P
Abstract : The alveolar content of fibres and asbestos bodies was assessed by bronchoalveolar lavage (BAL) in 21 asbestos sprayers. Transmission and scanning electron microscopy (TEM and SEM) and two light microscopical (LM) methods, cytocentrifugation, and Millipore filtration were used. The subjects had been exposed mainly to crocidolite asbestos for an average of 2.8 (range 0.2-13) years in 1950-75. The mean (median) total fibre count (of asbestos bodies and uncoated fibres) per ml of BAL fluid was 5500 (2800) by TEM and 2900 (1000) by SEM. The mean (median) count of asbestos bodies per ml with LM was 810 (500) with cytocentrifugation and 750 (480) with Millipore filtration, 840 (320) by TEM, and 1750 (420) by SEM. The mean proportion of coated fibres was 35% by TEM and 45% by SEM. The mean length of the coated fibres was 22 (range 4-65) microns by TEM and 34 (range 4.5-170) microns by SEM. The total fibre count exceeded 1000 fibres per ml in 70% of the cases by TEM. Asbestos body counts exceeded 1 per ml in 95% of the cases by LM. The fibre counts by SEM were in good accordance with counts by TEM except in a few cases in which the TEM result was considerably higher. In these cases the proportion of coated fibres was also low. All four counting methods appeared to give consistent results in heavily exposed cases when fibre load in the lungs was high. The counting of asbestos bodies may, however, underestimate the total alveolar fibre load in some cases.